Rational Expectations Business Cycles in Search Equilibrium - Diamond, Peter; Fudenberg, Drew (Journal of Political Economy, 1989)
We examine the rational expectations equilibrium paths of the model of search and barter in Diamond's "Aggregate Demand Management in Search Equilibrium." For some initial positions, there are two equilibrium paths converging to different steady states, with the high-activity path Pareto-dominating the low-activity path. With some parameters there is also a continuum of equilibrium paths converging to another steady state. Moreover, there can be cycles that are equilibrium paths, even though the environment is stationary.